ANALYSIS OF EMPLOYEE PERFORMANCE OF BANK ACEH SYARIAH, LHOKSEUMAWE CITY IN 2025 - Muhammad; M. Nazaruddin; Sufi; Teuku Zulkarnaen; Nur Hafni (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
In the era of globalization and digitalization, the banking industry faces increasingly complex challenges, such as intense competition, regulatory changes, and rising customer expectations for fast, secure, and high-quality services. In this context, employee performance becomes a key factor in determining the bank's ability to adapt and grow. Employee performance not only includes technical competence in carrying out banking tasks but also skills in serving customers, mitigating risks, and maintaining the institution's reputation and trust. Theoretically, this research is based on the concept of business administration, which views organizations as a series of interconnected activities to achieve objectives, including effective human resource management. In the workplace, employees' perceptions of their environment and the feedback provided by supervisors play an important role in shaping attitudes, motivation, and performance. This study employs a qualitative approach using in-depth interviews, direct observation, and documentation, resulting in a comprehensive understanding of employee performance dynamics in the field. The findings indicate that employees who consistently apply the principles of Amanah, Shiddiq, Fathanah, and Tabligh tend to receive constructive feedback that encourages performance improvement. Conversely, employees who are less optimal in applying these principles generally receive corrective feedback as a form of guidance. Properly delivered feedback has been shown to strengthen positive employee behavior, as explained in reinforcement theory, which states that behavior is more likely to be repeated when it results in favorable consequences. Overall, the performance of BAS Lhokseumawe Branch employees is categorized as good, as reflected in the achievement of targets and compliance with sharia principles. This study suggests that management should enhance the quality of communication in providing feedback, including through training for unit leaders to deliver objective, constructive, and empathetic feedback, thus improving employee motivation without creating psychological pressure.